2022
DOI: 10.1155/2022/6154233
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation Analysis of Vaspin Gene Polymorphisms and Polycystic Ovary Syndrome Based on Intelligent Medicine

Abstract: Polycystic ovary syndrome (PCOS) is now a common gynecological endocrine disease, also known as Stein–Leventhal syndrome. Studies have found that Vaspin gene polymorphism is significantly associated with diabetes and cardiovascular disease, and PCOS has a clear glucose metabolism abnormality. So far, because the cause of PCOS is not clear, many problems such as the etiology, diagnostic criteria, prevention, and treatment of PCOS remain unsolved. Which also makes PCOS attract the attention of academic circles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Genetic polymorphisms (SNPs) in the vaspin gene SERPINA12 were identified, which strongly correlated with vaspin serum levels with p -values up to 10 −35 , but no association with T2D or related traits were observed [ 179 ]. With regard to PCOS, in a very recent study including 40 women with PCOS and the same number of control individuals, the C allele of SNP C677T in the vaspin gene was reported to increase the risk of PCOS 2.077 times ( p < 0.05), and thus was suggested to be a genetic susceptibility marker for PCOS [ 180 ]. In a previous study including 150 women with PCOS and the same number of controls, the vaspin gene SNP rs2236242 exhibited significant differences in genotype frequencies between both groups (OR = 0.59, CI = 0.37–0.95, p = 0.03).…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Genetic polymorphisms (SNPs) in the vaspin gene SERPINA12 were identified, which strongly correlated with vaspin serum levels with p -values up to 10 −35 , but no association with T2D or related traits were observed [ 179 ]. With regard to PCOS, in a very recent study including 40 women with PCOS and the same number of control individuals, the C allele of SNP C677T in the vaspin gene was reported to increase the risk of PCOS 2.077 times ( p < 0.05), and thus was suggested to be a genetic susceptibility marker for PCOS [ 180 ]. In a previous study including 150 women with PCOS and the same number of controls, the vaspin gene SNP rs2236242 exhibited significant differences in genotype frequencies between both groups (OR = 0.59, CI = 0.37–0.95, p = 0.03).…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Computational Intelligence and Neuroscience has retracted the article titled "Correlation Analysis of Vaspin Gene Polymorphisms and Polycystic Ovary Syndrome Based on Intelligent Medicine" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Computational Intelligence and Neuroscience has retracted the article titled “Correlation Analysis of Vaspin Gene Polymorphisms and Polycystic Ovary Syndrome Based on Intelligent Medicine” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%